RELEVANSI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK ETIKA DAN KARAKTER PESERTA DIDIK SEKOLAH MENENGAH KEJURUAN DI KEHIDUPAN MODERN (Studi kasus di SMK Bandung Selatan 1 Bandung dan SMK Aqua Vitae) - Iriantara, Yosal; Ikoh, Ai; Hermawan, Agus; Abdul Kosim, Cucu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the relevance of Islamic Religious Education (IRE) in shaping the ethics and character of vocational high school students in modern life. The rapid development of digital technology, globalization, and changing social values poses moral and ethical challenges for students, particularly those in vocational education who are prepared to enter the world of work. This research aims to analyze the role, strategies, and relevance of Islamic Religious Education in forming ethical and character values among students at SMK Bandung Selatan 1 Bandung and SMK Aqua Vitae Bandung. The study employs a qualitative descriptive approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving school principals, Islamic education teachers, students, and relevant school documents. The findings reveal that Islamic Religious Education plays a significant role in developing students’ ethical behavior and character through contextual learning, teacher role modeling, religious habituation, and integration of Islamic values with modern life and work ethics. However, challenges such as limited instructional time, diverse student backgrounds, and the influence of digital culture remain obstacles. The study concludes that Islamic Religious Education remains highly relevant in fostering ethical, responsible, and morally grounded vocational school graduates when implemented contextually and supported by collaboration among schools, families, and communities.